Reinventing Ireland : culture, society, and the global economy - Cronin, Michael, 1960-; Gibbons, Luke; Kirby, Peadar (Contemporary Irish studies., 2002)
Critical account of the economic boom in Ireland and the neo-liberal culture that has accompanied it.